Emergence of NDM-1 on IncR-IncFIA (HI1) plasmid in carbapenem-resistant Kluyvera ascorbata from China - Zhang, Duo; Zhou, Di; Zheng, Shuai; Zhang, Xindan; Hou, Qinlong; Liu, Yang; Li, Shuang; Han, Huiming (Frontiers in Microbiology, 2025)
New Delhi metallo-β-lactamase 1 (NDM-1), a member of the B-type metallo-β-lactamase (MBL) family, emerged as a major focus in resistance research, raising serious concerns about the treatment of bacterial infections over the past decade. Kluyvera ascorbata, generally considered a bacterium of low pathogenicity and rarely associated with severe infections, has nonetheless demonstrated significant resistance to a broad spectrum of antibiotics in recent studies. In this study, we successfully isolated a K. ascorbata strain harboring the antibiotic-resistant genes blaNDM-1 and blaCTX-M-77 from a fecal sample of a patient with diarrhea in China. The strain was accurately identified using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). Additionally, the minimum inhibitory concentration (MIC) of the strain against various antimicrobial agents was determined using agar dilution and microdilution method. The results indicated that the strain exhibited resistance to all tested antimicrobial agents. The blaNDM-1 resistance gene was located on an IncFIA (HI1), IncR plasmid, as revealed by whole-genome sequencing. A detailed analysis of the plasmid’s size, number, and location was conducted using S1-nuclease pulsed-field gel electrophoresis (S1-PFGE), Southern blotting, and conjugation experiments. These experiments successfully demonstrated the transfer of the plasmid carrying blaNDM-1 into the recipient bacterium Escherichia coli EC600. These findings underscore the urgent need for continuous surveillance of the blaNDM-1-carrying plasmid in clinical isolate of K. ascorbata to prevent and contain its further dissemination in China.